2020
DOI: 10.1186/s12909-020-02016-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives of bedside teaching in an obstetrics, Gynaecology and neonatology hospital

Abstract: Background: Osler taught doctors to "have no teaching without a patient for a text, and the best teaching is that taught by the patient himself". Bedside teaching (BST) facilitates clinical practice of skills, teaches empathy, instils confidence and builds on patient-doctor relationships. However, its use has declined dramatically due to concerns regarding privacy and autonomy. Most of the research in this area concentrates on medical student or academic opinion of BST using survey based methods. This qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…14 Even in ob/gyn and neonatology departments, patients accepted bedside teaching as an important learning tool for students, and female patients saw themselves as contributing to teaching (‘patient as teacher’). 15 It has been observed that patients participate in bedside teaching with a sense of altruism. 16 …”
Section: Discussionmentioning
confidence: 99%
“…14 Even in ob/gyn and neonatology departments, patients accepted bedside teaching as an important learning tool for students, and female patients saw themselves as contributing to teaching (‘patient as teacher’). 15 It has been observed that patients participate in bedside teaching with a sense of altruism. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Two types of bedside teaching occur within this hospital, full details of which are published elsewhere [ 25 ]. In brief, the first type is a senior midwife led multidisciplinary team ward round occurring every morning and based on the principles of family centred care [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The second type is a teaching ward round occurring two to three times a week during term time, focused on education of medical students, following standard principles of Choice, Consent and Confidentiality [ 29 ] and led by trained medical educators. While the second type of BST was the focus of the qualitative research study [ 25 ], both types are referenced in the development of this questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the constantly decreased exposure of the undergraduate medical students to this critically important aspect of their teaching, they are lacking in mastering clinical skills (3). The reasons for the decline in bedside teaching are multiple; busy hospitals, increased patient turnover, busy senior clinical faculty, increase in paperwork with no extra time allotment for such tasks, increase in patient's privacy issues and legal aspects are the few common reasons (4). Incidences of preventable medical errors and patient safety concerns are a few other major concerns that have led to the decline in bedside teaching (5) (6).…”
Section: Introductionmentioning
confidence: 99%